The HMGA1-pseudogene7 shows oncogenic activity in vivo. Issue 22 (16th November 2020) - De Martino, Marco; Esposito, Francesco; Fusco, Alfredo
ABSTRACT: We have recently reported that transgenic mice overexpressing the HMGA1-pseudogene7 develop hematological neoplasia marked by monoclonal B-cell populations, and diagnosed as Diffuse Large B-cell Lymphoma. These findings prove the HMGA1-pseudogene7 oncogenic role in vivo .